Concerted evolution at a multicopy locus in the protozoan parasite Theileria parva: Extreme divergence of potential protein-coding sequences - Bishop, Richard P.; Musoke, A.J.; Morzaria, S.P.; Sohanpal, B.K.; Gobright, E.I. (1997)
Concerted evolution of multicopy gene families in vertebrates is recognized as an important force in the generation of biological novelty but has not been documented for the multicopy genes of protozoa. A multicopy locus, Tpr, which consists of tandemly arrayed open reading frames (ORFs) containing several repeated elements has been described for Theileria parva. Herein we show that probes derived from the 5'/N-terminal ends of ORFs in the genomic DNAs of T. parva Uganda (1,108 codons) and Boleni (699 codons) hybridized with multicopy sequences in homologous DNA but did not detect similar sequences in the DNa of 14 heterologous T. parva stocks and clones. The probe sequences were, however, protein coding accoring to predictive algorithms and codon usage. The 3'/C-terminal ends of the Uganda and Boleni ORFs exhibited 75 percent similarity and identity, respectively, to the previously identified Tpr1 and Tpr2 repetitive elements of T. parva Muguga. Tpr1-homologous sequences were detected in two additional species of Theileria. Eight different Tpr1-homologous transcripts were present in piroplasm mRNA from a single T. parva Muguga-infected animal. The Tpr1 and Tpr2 amino acid sequences contained six predicted membrane-associated segments. The ratio of synonymous to nonsynonymous substitutions indicates that Tpr1 evolves like protein-encoding DNA. The previously determined nucleotide sequence of the gene encoding the p67 antigen is completely identical in T. parva Muguga, Boleni, and Uganda, including the third base in codons. The data suggest that concerted evolution can lead to the radical divergence of coding sequences and that this can be a mechanism for the generation of novel genes.